The Effectiveness of the Quiz Team Learning Model on Islamic Education Learning Outcomes of Eighth-Grade Students at SMP Negeri 2 Tinambung - Randi Sudirman; Marjanah Marjanah (Lembaga Yasin AlSys, 2026)
Improving learning outcomes in Islamic Education requires instructional models that strengthen engagement, conceptual mastery, and formative interaction; however, empirical evidence on the effectiveness of Quiz Team active learning in junior secondary Pendidikan Agama Islam (PAI) remains limited. This study evaluated the effectiveness of the Quiz Team active-learning model in improving PAI learning outcomes among eighth-grade students at SMP Negeri 2 Tinambung. A one-group pretest–posttest pre-experimental design was employed, involving 29 students who received Quiz Team instruction across five meetings. Data were collected using validated multiple-choice pretests and posttests, supported by standardized classroom implementation observations. Descriptive statistics, Kolmogorov–Smirnov normality testing, Levene’s homogeneity testing, and a paired-sample t-test at α = 0.05 were conducted using SPSS, with effect size reporting accompanying the inferential analysis. The findings showed that implementation fidelity improved across sessions from 82.95% to 89.77% and 92.04%, indicating rapid adaptation by teachers and students. Students’ initial mastery was low in the pretest (M = 35.07, SD = 8.14), whereas posttest scores increased substantially (M = 78.79, SD = 6.89), with a mean gain of 43.65 points. Statistical assumptions were met, including normality for pretest and posttest scores (p = 0.816 and p = 0.863) and homogeneity (p = 0.383). The paired-sample t-test confirmed a highly significant improvement in learning outcomes (t = 28.152, p < 0.001). These findings suggest that Quiz Team instruction, through retrieval practice, peer explanation, and rapid formative feedback, can enhance student engagement and conceptual mastery in PAI. The study contributes to active-learning literature in Islamic Education by providing empirical evidence on the potential value of Quiz Team instruction, although its single-group design and single-site sample limit causal inference and generalizability. Future studies should employ controlled designs, larger and more diverse samples, longer follow-up periods to assess retention, and process evaluations to identify the active components that support scalable implementation.